Karakteristik dan Sumber Resiko dalam Era Modernisasi Refleksif - - Suharko (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 1997)
Modernization has reached a level of social development, that is reflexive modernization, which distinct with simple modernization. Reflexive modernization has a higher level of risk or uncertainty, that is manufactured risk or uncertainty. The manufactured risk appears as large-scale hazard,both in term of space or time. The risk tend to be refractory hazard and it is very difficult to control and manage. The sources of manufactured risk relate with the limitations of modern institutions, which arise in form: economic polarization, ecological threats, threats of large-scale war, and denial of democratic rights. According to Giddens, the splving of risk need to reform those problems by radical politics,